MARKSTRAT3 : the strategic marketing simulation - Larréché, Jean-Claude. (South-Western College, 1998)
This book is about: Markstrat; Market research; Operating instructions; Marketing planning; Market segmentation and positioning; The marketing and R&D interface; Consumer analysis; Competitive strategies; Allocation of resources; ...